Pengaruh Financial Technology Terhadap Kinerja Keuangan Perbankan - Tambunan, Marintan; Aziza, Nurna (Politeknik Ganesha Medan, 2024)
The development of information and communication technology has brought significant changes in various aspects of human life. One aspect that has been greatly affected is the banking sector. The digital revolution has changed the way banking operates, especially in terms of customer service and financial management. This study aims to see how the influence of Internet Banking and Mobile Banking on financial performance in banks as measured by Return On Assets (ROA), Return On Equity (ROE), Capital Adequency Ratio (CAR), Non Performing Loan (NPL). The population in this study are banks listed on the Indonesia Stock Exchange (BEI). The method used is non probability sampling method with purposive sampling technique and obtained 10 banks used as samples for the research period for 3 years (2020-2022). The data analysis technique used is Structural Equation Modeling Partial Least Square (SEM-PLS) with the help of SmartPLS (v. 4) software as a data analysis tool. The results of this study indicate that Internet banking has no effect on ROA, CAR and NPL but has a significant negative effect when measured by ROE. Mobile banking has a negative effect on financial performance calculated using NPL but mobile banking has no effect on ROA, ROE and CAR. Future research is expected to add other variables that have an influence on financial performance in banking and increase the number of research periods.